2000
DOI: 10.3147/jsfp.35.61
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cortisol on the Degranulation of Eosinophilic Granular Cells in Tilapia.

Abstract: ABSTRACT-We examined the effect of cortisol on the degranulation and number of eosinophilic granular cells (EGCs) in tilapia, Oreochromis niloticus. One hour after injection of stimulants (killed Escherichia coli or substance P, a neurotransmitter) into the swim bladder, the percent of the degranulated EGCs in the swim bladder membrane was determined. Peritoneal implantation of coconut oil containing cortisol (50 mg/kg body weight) 24 h before injection of stimulants signifi cantly reduced the percent of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Further studies have also indicated that these cells respond to short-term stress, such as handling, by migrating to specific tissue sites, notably the gills (Holland and Rowley 1998). Implants or injections of cortisol, however, have been shown to inhibit the degranulation of EGCs in tilapia swim bladder membrane (Matsuyama et al 2000). This suggests potential differences in the response of EGCs to shortterm versus long-term stress and generally indicates that these cells are an important part of the short-term inflammatory response in fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have also indicated that these cells respond to short-term stress, such as handling, by migrating to specific tissue sites, notably the gills (Holland and Rowley 1998). Implants or injections of cortisol, however, have been shown to inhibit the degranulation of EGCs in tilapia swim bladder membrane (Matsuyama et al 2000). This suggests potential differences in the response of EGCs to shortterm versus long-term stress and generally indicates that these cells are an important part of the short-term inflammatory response in fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, MCs are involved in the fish nonspecific immunity, and are able to defense against many immune stimulations through degranulation. 92,93 After infected by C. irritans, ISH results showed that the amounts of positive MCs presenting obvious changes around the parasite at the site of infected-L. crocea. 34 It is speculated that the recruitment of MCs in fish is responsible for immunomodulation and inflammatory responses to C. irritans infection.…”
Section: Non-specific Mechanismsmentioning
confidence: 96%
“…For macrophages, after infection with C. irritans , expression of macrophage expressed gene 1 ( Ecmpeg1 ) was significantly up‐regulated in the spleen and gills and the Ecmpeg1 positive cells were determined in gills, 39,91 implying that Ecmpeg1 positive cells might be involved in antiparasitic activity against C. irritans infection. Generally, MCs are involved in the fish non‐specific immunity, and are able to defense against many immune stimulations through degranulation 92,93 . After infected by C. irritans , ISH results showed that the amounts of positive MCs presenting obvious changes around the parasite at the site of infected‐ L. crocea 34 .…”
Section: Irritans‐marine Teleost Immune Responses As a Model For Unde...mentioning
confidence: 99%
“…A similar study using the hamster cheek pouch has been reported (Oda and Katori, 1992), in which they demon strated the inhibition of the abilities of polymorpho nuclear leukocyte to pass through endothelial cells and vascular wall, and, moreover, to migrate toward a certain site were caused by dexamethason, which is akin to cortisol. The inhibition of degranulation in fish mast cells by cortisol could be involved in less migration of neutrophils (Matsuyama et al, 2000). On the other hand, Weyts et al (1998) reported that the cortisol did not affect carp neutrophil respiratory burst activity and suppressed the carp neutrophil apoptosis.…”
Section: Neutrophil Activitiesmentioning
confidence: 99%